2011
DOI: 10.4028/www.scientific.net/amr.301-303.26
|View full text |Cite
|
Sign up to set email alerts
|

A Dissertation on Polysiloxane-Antifoaming-Agents: Antifoaming Principles, Synthesis and Compound

Abstract: This first part of this paper will introduce the mechanical-dynamical properties of polysiloxane defoamer thoroughly. Defoamers or foam breakers are added to eliminate the existing foam and usually act on the outer surface of the foam because a bubble is a closed system and the defoamer can only reach the outer surfaces. Then, some of synthesis methods and compounds under real application conditions are given, such as synthesis of methyl hydrogen silicone oil, synthesis methods of polyether and compounds of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…An antifoam having low viscosity helps the defoamer to disperse easily in the foaming medium but has poor performance in bubble suppression. On the other hand, high viscosity antifoams destroy foam at a slower rate as compared to low viscosity antifoams, but they perform better on more stable and persistent foams . In general, low viscosity antifoams are preferred as they exhibit both insolubility in foaming medium and lower surface tension than the medium that they are applied to .…”
Section: Selection Criteria For Antifoam In Gas Sweeteningmentioning
confidence: 99%
See 2 more Smart Citations
“…An antifoam having low viscosity helps the defoamer to disperse easily in the foaming medium but has poor performance in bubble suppression. On the other hand, high viscosity antifoams destroy foam at a slower rate as compared to low viscosity antifoams, but they perform better on more stable and persistent foams . In general, low viscosity antifoams are preferred as they exhibit both insolubility in foaming medium and lower surface tension than the medium that they are applied to .…”
Section: Selection Criteria For Antifoam In Gas Sweeteningmentioning
confidence: 99%
“…In recent years, modified silicone antifoams have widely been used in foaming liquid in various industries as they possess various antifoaming properties such as having low- and high-temperature resistance, low surface tension, chemically inertness, and no physiological toxicity . For instance, a multicomponent antifoam consisting of polyether-modified silicone has shown excellent potential as an antifoaming agent . Another study demonstrated that the use of antifoam mainly consisting of PPG and a small amount of hydrophobic silica could improve the defoaming ability.…”
Section: Opportunities and Challenges Of Antifoams In Acid Gas Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified silicone defoamers mainly have improved emulsified performance of the polysiloxane defoamer by introducing a hydrophilic group of polyorganosiloxane, thus exhibiting excellent foaming properties and water solubility. 8 Besides, studies show that polysiloxane cannot be used directly as a defoamer in an oily system. 9 , 10 Therefore, the structure and performance of polysiloxane are typically modified when applied in an oily system.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of silicone oil also plays a vital role in water solubility and surface activity of polyether-modified polysiloxane antifoaming agents. 4 , 8 …”
Section: Introductionmentioning
confidence: 99%